Updating the distribution range of Chrysocyon brachyurus (Mammalia: Carnivora) in Argentina - Orozco, Maria Marcela (2022)
The maned wolf Chrysocyon brachyurus, the fourth largest canid, is categorized as Near Threatened on the IUCN Red List. The objectives of this study were to update information on the occurrence of this species in Argentina, compare the current distribution to that previously described for –, and indicate the areas in which the species is exposed to particular hazards. We created a database that included , new records of C. brachyurus for –, in addition to records for –  that had not been reported previously. We calculated the area of occupancy of the species in Argentina to be , km . Most of the new records of C. brachyurus are in the Chaco Seco, Espinal and Pampas ecoregions. Our findings indicate a current area of occupancy % higher than that calculated from records for –. However the location and frequency of reported threats and the intense environmental transformation that characterizes the areas for which we obtained new records suggest counterintuitive implications for the conservation of the species because of increased human–wildlife interactions. Our study reveals the need for systematic research to improve the understanding of the ecological processes that affect the maned wolf in Argentina, and will aid in the development of conservation strategies for the species.